The Effect of Compensation on Employee Performance at KSU Tandangsari, Tanjungsari District, Sumedang Regency - Eka Sri Rahayu; Helles Amanda; Khisty Hanila Dewi (SINTESA, 2022)
KSU Tandangsari is a cooperative engaged in dairy farming in the Tanjungsari District. The cooperative is experiencing problems with decreasing the level of employee performance. Therefore, this study aims to determine how much influence compensation has on employee performance at KSU Tandangsari. This research method uses descriptive analysis with a quantitative research approach. Sampling was done by simple random sampling. The research data were analyzed using simple regression analysis, correlation coefficient analysis, coefficient of determination analysis and t test using SPSS software to analyze the research data. The results of the study explain that compensation has a low relationship with employee performance as indicated by the correlation coefficient of 0.314. The results of the regression analysis show that compensation has a positive and significant effect on employee performance. This is evidenced by the simple regression equation model Y= 55,823 + 0.415 X, the significance value is 0.008 which is smaller than 0.05 and the tcount (2.739) is greater than ttable (1.671). Then based on the analysis of the coefficient of determination, compensation has an effect of 11.0% on employee performance, while the remaining 89.0% is influenced by other factors not examined.